Determinantes dos indicadores sociais dos municípios cearenses: análises para o período de 1991 a 2010 - Monteiro, Marcelo de Sousa (2014)
The motto of public policies in Brazil has been guided by the search for overcoming poverty rates and improvement of living conditions of the population. In this sense, the verification of the effectiveness of such policies have focused on evaluating indicators such as health, education and income, individually or consolidated, as viewed from the human development indicator. This study aims to evaluate the situation of social indicators, mainly health and life expectancy at birth, infant mortality and the Municipal Human Development Index (IDHM),using data from 184 municipalities in Ceara State, with information from demographic census, conducted by the Brazilian Institute of Geography and Statistics (IBGE) in the years of 1991, 2000 and 2010, extracted from the Atlas of Human Development in Brazil 2013. The descriptive analysis of the data, indicated, a priori, that the municipalities of Ceara showed a significant improvement in social indicators, as well as a reduction in the disparity. Regarding the econometric models, in general, estimated by fixed effects, it was found that the main determinant is education, or the lack of it, with emphasis on adult illiteracy.